The CBM time-of-flight wall: a conceptual design - Deppner, Ingo Martin; Herrmann, Norbert (Journal of Instrumentation, 2014)
Charged hadron identification in the Compressed Baryonic Matter experiment (CBM) is realized via the Time-of-Flight method [1]. For this purpose the CBM-ToF collaboration designed a Time-of-Flight wall composed of Multi-gap Resistive Plate Chambers (MRPCs). Due to the high interaction rate in CBM of 10 MHz the key challenge is the development of high rate MRPCs above 25 kHz/cm2 which become possible after the development of low resistive glass with extremely good quality. In this article we present the actual conceptual design of the ToF-wall which is subdivided in three parts namely the outer wall, the inner wall and the forward zone that are discussed in detail.